The Mental Health Impact of Online Gender-Based Sexual Violence on Adolescent Girls - Zara Zafar (Inquiry@Queen's Undergraduate Research Conference Proceedings, 2026)
The rise of digital technologies has coincided with increased technology-facilitated gender-based sexual violence (TF-GBSV), including online sexual harassment, sextortion, and non-consensual image sharing. Adolescents (especially girls and gender-diverse youth) are disproportionately affected, with exposure linked to depression, anxiety, low self-esteem, and other adverse mental health outcomes. This systematic review examined associations between F-GBSV and mental health among adolescent girls, including cisgender, transgender, and sexual minority youth. Following PRISMA guidelines, five databases were searched through June 2025. Eligible studies included adolescents aged 14-18 years exposed to TF-GBSV with reported mental health outcomes. Data was extracted and assessed using the Joanna Briggs Institute and COSMIN tools. Fifteen studies (12 cross-sectional, 2 longitudinal, 1 qualitative) representing 11 countries met the inclusion criteria. Online sexual harassment (87%) and non-consensual image sharing (80%) were the most studied forms, with nearly half reporting polyvictimization. TF-GBSV exposure was consistently linked to poorer mental health, including depression (73%), anxiety (67%), psychological distress (40%), as well as lower self-esteem, suicidality, and substance use. Polyvictimization predicted the most severe outcomes, and gender-diverse/LGBTQ+ adolescents experienced greater psychological harm than cisgender peers. Qualitative findings emphasized fear, shame, institutional neglect, and heightened distress. Overall, TF-GBSV represents a significant risk to adolescent mental health, particularly for marginalized gender and sexual identities. These results underscore the need for trauma-informed prevention, inclusive policies, and tailored mental health support. Longitudinal and culturally diverse research is needed to clarify long-term effects and guide interventions.